Indication and surgical consideration of cochlear implantation at Ramathibodi Hospital - Chanida Kanchanalarp (2018)
Objectives: To demonstrate selection criteria for cochlear implant candidates as well as the outcome of quality of life (QoL) after cochlear implant surgery. Material and Method: Retrospective review was performed of all cochlear implants at Ramathibodi Hospital. A total number of 33 cochlear implantations were performed during the period of 10 years from December 1995 to December 2005. Inclusion criteria were established and the audiological criteria were then evaluated using the electrical promontory stimulation test. The etiology of severe sensory neural hearing loss was detected. The CT scan and MRI of the inner ear were studied in the different causes of deafness. Results: The main cause of deafness in the present study (16 adults and 17 children) was suffering from pregnancy rubella. The second one was familial congenital deafness. The CT scan studied in the rubella cases showed anatomical normal cochlea and the hereditary cause of deafness showed abnormal cochlea that caused a strong perilymphatic gusher in a 14 year- old boy. There were 16 cases of adolescent and adult patients who all had good response in the promontory stimulation test. The QoL post implantation was evaluated in regards to improvement in education and communication. Conclusion: Multi-channel cochlear implantation in severe profound hearing loss patients could improve the hearing in both normal and abnormal cochlea, congenital rubella deafness and the familial cause of deafness. The outcomes of the QoL after surgery were better in hearing detection, speech perception, school performance, communication and return to work.